Ordenamiento territorial y concesiones mineras en el Perú: bases para un sistema integrado y armónico con el desarrollo sostenible - Chinchay Tuesta, Ady; Scurrah, Martin (Pontificia Universidad Católica del Perú, 2024)
Mining and other economic activities are carried out on a particular territory and, thus, affect the natural and human environment in which they operate. As a consequence and in order to avoid future and eventual socio-environmental conflicts, it is essential to guarantee that these human activities are conducted in a manner that respects both environment and society. One of the most powerful tools to achieve this balance between human activities and sustainable development is Land-Use Planning (LUP), understood as the institution charged with organizing human activities to achieve that balance. Bearing this in mind, the present article has three objectives: a) complement the literature on LUP by explaining the interconnection between LUP and the mining concessions regime, b) identify and analyze the main problems with the procedures for granting mining concessions in Peru, and c) propose the foundations for a future integrated system of mining concessions and LUP based on common principles and participatory mechanisms to reconcile tensions between the interests and values of all stakeholders, in addition to providing alternative solutions to the current problems with the mining concessions regime. To analyze the mining concessions regime and LUP a qualitative methodology is adopted, combining documentary analysis, review of official reports, and semi-structured interviews with key actors. Taking into consideration the stated objectives, this research concludes that: a) to achieve sustainable development and prevent the future emergence of conflicts, mining concessions must be granted based on territorial planning that the State (at the national, regional and local levels) should undertake prior to and in conjunction with civil society; b) the mining concession procedure lacks mechanisms of good governance, environmental sustainability and social justice; and c) as an alternative solution to these issues, this research suggests the creation of an integrated system of LUP and mining concessions, one that is binding, efficient, gradual, investor-friendly and intercultural.

Las actividades mineras y demás actividades económicas se realizan sobre el territorio; por ende, influyen en el ambiente y el entorno humano en el que se desenvuelven. Por ello, es trascendental garantizar que estas actividades humanas sean ejecutadas de forma respetuosa con el ambiente y la sociedad para así evitar futuros y eventuales conflictos socioambientales. Una de las herramientas más poderosas para lograr este equilibrio entre actividades humanas y desarrollo sostenible es el ordenamiento territorial (OT), entendido como la institución encargada de organizar las actividades humanas para lograr dicho equilibrio. Con base en esta premisa, este artículo tiene un triple objetivo: a) complementa la literatura sobre OT, explicando la interconexión entre esta institución y el régimen de concesiones mineras; b) identifica y analiza los principales problemas del procedimiento de otorgamiento de concesiones mineras en el Perú; y c) propone los fundamentos de un futuro sistema integrado de concesiones mineras y OT que contiene principios comunes y mecanismos participativos para conciliar las tensiones entre los intereses y valores de todos los interesados, además de brindar alternativas de solución a los problemas actuales del régimen de concesiones mineras. Para ello, se adopta una metodología cualitativa que combina análisis documental, revisión de reportes oficiales y entrevistas semiestructuradas con actores clave. Teniendo en cuenta los objetivos planteados, esta investigación concluye que: a) para lograr el desarrollo sostenible y evitar la futura aparición de conflictos, las concesiones mineras deben ser otorgadas con base en una planificación del territorio que el Estado (a nivel nacional, regional y local) debe realizar previa y conjuntamente con la sociedad civil; b) el procedimiento de concesiones mineras carece de mecanismos de buena gobernanza, sostenibilidad ambiental y justicia social; y c) como alternativa de solución a dichos problemas, se sugiere la creación de un sistema integrado de OT y concesiones mineras que sea vinculante, eficiente, escalonado, amigable con los inversionistas e intercultural.
Land-Use Planning and Mining Concessions in Peru: Foundations for an Integrated System Compatible with Sustainable Development
Keywords: Land-use planning; Ecological-economic zoning; Multi-level planning; Extractive industries; State capacity; Socio-environmental conflicts; Ordenamiento territorial; Zonificación económica-ecológica; Planeamiento multinivel; Industrias extractivas; Capacidad estatal; Conflictos socioambientales; https://purl.org/pe-repo/ocde/ford#5.05.01